Cultural Values and Human Resource Outcomes in the Nigerian Banking Industry - Olusegun Atiku, Sulaiman; Fields, Ziska; Abe, Ethel (SPOUDAI Journal of Economics and Business, 2017)
This article explores the interplay between the cultural values and human resource (HR) outcomes in the Nigerian banking sector. The article adopted a quantitative method, utilising a correlational approach with the advanced explanatory design. A combination of simple random sampling and convenience sampling techniques was adopted, three hundred and eighty (380) questionnaires were distributed to respondents at two selected banks. Three hundred and five (305) questionnaires were properly completed and returned. The exploratory factor analysis, scale reliability and validity, and bivariate correlations between the variables were statistically verified. The confirmatory factor analysis (CFA) of the proposed model explaining the link between cultural values and HR outcomes was tested using Structural Equation Modelling (SEM). The findings revealed that there were significant positive relationships between cultural values and HR outcomes in the Nigerian banking sector. This study concludes that employees’ competence and satisfaction with job fulfilment were most important HR outcomes in the Nigerian banking industry. This article is valuable in recommending improved co-workers and supervisor directed behavioural patterns in the Nigerian banking industry. The managerial implication dwells on the need for deliberate alignment of emerging corporate strategies and core values to improve co-workers/organisational directed behaviours in the Nigerian banking industry. JEL Classification: M140, M500